The Perceived Curriculum Development among EFL Cambodian Lower Secondary Teachers - Siem Or (MASI Mandiri Edukasi, 2025)
The issue of teachers’ participation in school decision-making remains a complex and enduring topic of educational research. This study examines the extent to which English language teachers in lower secondary schools in Phnom Penh, Cambodia, engage in curriculum development. Adopting an exploratory design, data were collected through questionnaires administered to 40 Cambodian EFL teachers, followed by in-depth interviews with six participants to obtain qualitative insights. The findings indicate that teachers’ involvement in curriculum development is limited and insufficiently institutionalized, with many respondents reporting low confidence in their decision-making capacities yet expressing a strong aspiration to contribute more actively. Namely, many teachers felt dissatisfied with their restricted role in curriculum-related decisions. The results also reveal the dominance of a top-down management structure and the absence of a collaborative professional culture that recognizes teachers as legitimate stakeholders in curricular decision-making. These findings suggest an urgent need for policy reforms that institutionalize participatory mechanisms, enhance teachers’ professional agency, and foster a more inclusive and dialogic approach to curriculum development in Cambodian schools.